2021
DOI: 10.1101/2021.07.07.451547
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mutualism-enhancing mutations dominate early adaptation in a microbial community

Abstract: Evolutionary dynamics in ecological communities are often repeatable, but how species interactions affect the distribution of evolutionary outcomes at different levels of biological organization is unclear. Here, we use barcode lineage tracking to experimentally address this gap in a facultatively mutualistic community formed by the alga Chlamydomonas reinhardtii and the yeast Saccharomyces cerevisiae. We find that interactions with the alga alter the magnitude but not the sign of the fitness effects of adapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 147 publications
(267 reference statements)
0
16
0
Order By: Relevance
“…the relative abundances of all species) after the member species evolved all together compared to them having evolved alone [152]. In contrast, Venkataram et al found that the interaction between yeast Saccharomyces cerevisiae and alga Chlamydomonas reinhardtii shifted more repeatably towards stronger mutualism when yeast evolved in the presence of the alga than alone [171]. Thus, species interactions appear to affect repeatability, but further studies will be needed to understand this effect.…”
Section: Community Evolution In the Labmentioning
confidence: 98%
See 2 more Smart Citations
“…the relative abundances of all species) after the member species evolved all together compared to them having evolved alone [152]. In contrast, Venkataram et al found that the interaction between yeast Saccharomyces cerevisiae and alga Chlamydomonas reinhardtii shifted more repeatably towards stronger mutualism when yeast evolved in the presence of the alga than alone [171]. Thus, species interactions appear to affect repeatability, but further studies will be needed to understand this effect.…”
Section: Community Evolution In the Labmentioning
confidence: 98%
“…In Box 3, we use the study by Meroz et al [158] to illustrate the potential for community evolution experiments to address some of these questions. While research in these directions is at its earliest stages, the initial results are encouraging [152,158,171]. One important potential outcome of this work would be to identify general rules for predicting a system's evolutionary repeatability based on its features.…”
Section: Which Features Of the Community Predict The Repeatability Of...mentioning
confidence: 98%
See 1 more Smart Citation
“…That evolutionary and ecological changes often go together has been most clearly shown in controlled experiments on synthetic microbial communities: evolution can change the way microbes consume resources or otherwise interact with each other (1115). This leads to environmental changes that modify selection pressures, forcing lineages into new evolutionary paths (1621). Complex adaptive landscapes have been hypothesized to chiefly shape the feedback between ecology and evolution in microbial communities (19, 22), but it is still unclear how diversification and other ecological shifts change those landscapes.…”
Section: Introductionmentioning
confidence: 99%
“…While application of barcoding initially focussed on adaptive evolution in single populations of model microbes, particularly yeast ( Saccharomyces cerevisiae ) (Blundell and Levy 2014; Cvijović et al 2018) and Escherichia coli (Jasinska et al 2020), strategies have since been devised for studying the evolution of cancer using barcoded lung cancer cells in mice (Rogers et al 2018) and quantification of eco-evolutionary dynamics in microbial communities (Venkataram et al 2022). The potential for extending strategies and applications is considerable, ranging from tracing object provenance (Nguyen Ba et al 2022), enhancing experimental power through mutant-multiplexing (Jackson et al 2020), extending understanding of microbiome transmission (Vasquez et al 2021), to the study of demographic changes during colonisation of new environments (Brettner et al 2022).…”
Section: Introductionmentioning
confidence: 99%